GUIDING PRINCIPLES ON BUSINESS AND HUMAN RIGHTS: THE IMPORTANT ATTEMPT TO ADDRESS CORPORATE HUMAN RIGHTS ABUSES - Topić, Boris V. (Pravni zapisi, 2020)
The rapid increase of power of transnational corporations and other business enterprises prompted initiatives for the international legal regulation of these entities with regard to human rights. This paper provides a critical overview of the first globally accepted standard that regulates human rights responsibilities of transnational corporations, namely the United Nations Guiding Principles on Business and Human Rights (UNGPs) - an international instrument consisting of 31 principles implementing the United Nations ‘Protect, Respect and Remedy’ framework on this issue of human rights and transnational corporations, and other business enterprises.The paper examines the UNGPs’ three pillars: a) the state duty to protect human rights; b) the corporate responsibility to protect human rights; and c) access to remedy for victims of corporate violations of human rights. It also provides a brief introduction to initiatives that preceded the UNGPs. While presenting the advantages of addressing the business-related human rights abuses through the soft law instrument, the paper also addresses a number of shortcomings of the soft law approach that underlie the UNGPs.
Keywords: United Nations Guiding Principles on Business and Human Rights; transnational corporations; corporate human rights violations; human rights due diligence; soft law